The True Cause of Coronary Artery Disease; Cholesterol is Irrelevant - David Rowland (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
This report is a synthesis of 22 studies which concludes that coronary artery disease is caused by free radical damage to tumor suppressor genes, which mutation allows cells to proliferate out of control to create benign mini tumors between the endothelium lining and the smooth muscle walls of arteries. As these tumors grow, they cause tiny tears in the endothelium that are patched with interlacing filaments of fibrin. This rough scar tissue traps minerals (especially calcium), heavy metals, macrophages, and cellular debris. The final smooth layer of cholesterol that is applied over this arterial plaque plays no causal part in its development. Recent studies indicate that nearly 75 percent of patients hospitalized for a heart attack had cholesterol levels which indicate they were not at high risk for a cardiovascular event, according to current national cholesterol guidelines. Thus, there is no causal relation between serum cholesterol levels and coronary artery disease.